Physicochemical Characterization And Diagnostic Leaching Of Complex Copper-Gold Ore - Mohd Bukhori, Muhammad Aiman (Universiti Sains Malaysia, 2022)
In this study, the gold ores were obtained from East Malaysia. Four samples were obtained from each different vein. The goal of this research was to identify the associated minerals and the deportment of gold in the collected samples. Numerous characterization analyses were carried out to explore the morphology, chemical content and identification of mineral phases using optical microscope, XRF, XRD, and FESEM analysis. The majority of the samples' composition made up of quartz, aluminosilicates, and carbonaceous elements; pyrite, chalcopyrite, arsenopyrite, magnetite, and hematite. From the polish section sample under optical microscopy, pyrite, and quartz grains was identified. Two methods were conducted in order to determine the gold content in the samples, which are fire assay analysis and bottle roll test. The highest gold content among the sample is JIRA with 56.98 g/t and the highest free milling bottle roll ore sample obtained is also JIRA with 2.548 g/t. The diagnostic leaching experiment was conducted on JIRA sample only, highest recovery obtained from direct cyanidation giving results of 52.74%. From the result, it can be concluded that the gold ore is refractory type as direct cyanidation gives recovery less than 80%.